Pulsating one-dimensional detonation in ammonia-hydrogen–air mixtures. (12th June 2022) - Zhu, Ruixuan; Fang, Xiaohang; Xu, Chao; Zhao, Majie; Zhang, Huangwei; Davy, Martin
Abstract: In this study, one-dimensional detonations in ammonia/hydrogen-air mixtures are numerically investigated by solving the fully compressible Navier-Stokes equations with detailed chemistry. Pulsating instabilities with single-mode are observed during the detonation wave propagation, accompanied by periodic coupling and decoupling of the lead shock wave and the reactive front. The ratio between driver pressure and initial pressure determines the overdrive degree and thus the oscillatory mode of detonation for a premixture with certain composition. The effects of hydrogen dilution and mixture equivalence ratio on pulsating detonations are also examined under a constant driver pressure. The growing hydrogen fraction in fuel blends significantly increases the oscillation frequency. In addition, the pulsating detonation frequency rises with increasing equivalence ratio under fuel-lean conditions, peaks under stoichiometric conditions, and falls under fuel-rich conditions as the equivalence ratio increases further. Evolutions of reactants, main intermediate radicals, and products are analysed in both fuel-lean and fuel-rich conditions. A chemical explosive mode analysis further confirms the highly-autoignitive nature of the mixture in the induction zone between reaction front and shock front where thermal diffusion plays a negligible role. Highlights: Numerical study of one-dimensional pulsating detonation is performed. Ammonia and hydrogen fuel blends with various compositions are considered. The effects of driver pressure and fuel/air equivalence ratio are examined. Different pulsating detonation frequencies are observed from parametric studies. Chemical explosive mode analysis reveals chemistry dominates thermal diffusion at detonation front.